Gender differences in socioeconomic inequality of alcohol‐attributable mortality: A systematic review and meta‐analysis. (8th August 2014) - Probst, Charlotte; Roerecke, Michael; Behrendt, Silke; Rehm, Jürgen
Abstract Introduction and Aims The present analysis contributes to understanding the societal distribution of alcohol‐attributable harm by investigating socioeconomic inequality and related gender differences in alcohol‐attributable mortality. Design and Methods A systematic literature search was performed on Web of Science, MEDLINE, PsycINFO and ETOH from their inception until February 2013. Articles were included when they reported data on alcohol‐attributable mortality by socioeconomic status (SES), operationalised as education, occupation, employment status or income. Gender‐specific relative risks (RR) comparing low with high SES were pooled using random effects meta‐analyses. Gender differences were additionally investigated in random effects meta‐regressions. Results Nineteen articles from 14 countries were included. For women, significant RRs across all measures of SES, except employment status, were found, ranging between 1.75 [95% confidence interval (CI) 1.21–2.54; occupation] and 4.78 (95% CI 2.57–8.87; income). For men, all measures of SES showed significant RRs ranging between 2.88 (95% CI 2.45–3.40; income) and 12.25 (95% CI 11.45–13.10; employment status). While RRs for men were in general slightly higher, only for occupation this gender difference was above chance (P = 0.01). Results refer to deaths 100% attributable to alcohol. Discussion and Conclusions The results are predominantly based on data from high‐income countries, limiting generalisability. Alcohol‐attributable mortality is strongly distributed to the disadvantage of persons with a low SES. Marked gender differences in this inequality were found for occupation. Possibly male‐dominated occupations of low SES were more strongly related to risky drinking cultures compared with female‐dominated occupations of the same SES.